Phaeohyphomycosis in China - He, Yun; Zheng, Hai-lin; Mei, Huan; Lv, Gui-xia; Liu, Wei-da; Li, Xiao-fang (Frontiers in Cellular and Infection Microbiology, 2022)
Background Due to more attention paid to melanized fungi over the past few decades and under the background of global COVID-19 pandemic, the virus itself and the immunosuppressive agents such as glucocorticoid further increases the risk of infection of deep mycoses. The number of patients with PHM has a tendency for rapid growth in the future. Their spectrum is broad and the early diagnosis and treatments are extremely sticky. This study aims to more comprehensively understand the clinical features of PHM in China over 35 years and to established a more applicable systematically classification and severity grades of lesions to guide treatment and prognosis. Methods We reviewed 174 cases of proven phaeohyphomycosis reported in Chinese and English language literature from 1987 to 2021 and we also made accurate classification definition and detail information arrangement of the epidemiology, species of clinical dematiaceous fungi, MIC values, clinical features, treatment and prognosis et al. Results The mortality of CNS, disseminated and pulmonary PHMs are 55%, 36% and 25%. Nearly 19% patients had poor quality-of-lives caused by complications such as disability, disfigurement and blindness. The overall misdiagnosis rate of PHM was 74%. Moderate to severe rashes are accounting for 82% in subcutaneous PHM. The head and face are mostly affected accounting for 16% in severe rashes. Nearly 30% invasive infections of PHM start from recurrent lesions. Voriconazole, itraconazole, L-AmB and terbinafine were most commonly used but treatment and prognosis of PHM remains challenging in reality. Conclusions Our classifications are more practical and easier to popularize, and non-specific rashes also have tons of characteristics. There’re no significant variations in curative rate, or death rate between three grades of lesions. But patients with severe rashes have much longer courses and the effective rate is relatively lower.